Savings and trust : the rise and betrayal of the Freedman's Bank - Hill Edwards, Justene (W.W. Norton & Company, 2024)
"In the years immediately after the Civil War, tens of thousands of former slaves deposited millions of dollars into the Freedman's Bank. African Americans envisioned this new bank as a launching pad for economic growth and self-determination. But only nine years after it opened, their trust was betrayed and the Freedman's Bank collapsed. Fully informed by new archival findings, historian Justene Hill Edwards unearths a major turning point in American history in this comprehensive account of the Freedman's Bank and its depositors. She illuminates the hope with which the bank was first envisioned and demonstrates the significant setback that the sabotage of the bank caused in the fight for economic autonomy. Hill Edwards argues for a new interpretation of its tragic failure: the bank's white financiers drove the bank into the ground, not Fredrick Douglass, its final president, or its Black depositors and cashiers. A story filled with both well-known figures like Abraham Lincoln, Frederick Douglass, Jay and Henry Cooke, and General O. O. Howard, and less well-known figures like Dr. Charles B. Purvis, John Mercer Langston, Congressman Robert Smalls, and Ellen Baptiste Lubin. This book can be used to understand the roots of racial economic inequality in America." --